1986
DOI: 10.1017/s0022172400066286
|View full text |Cite
|
Sign up to set email alerts
|

Purified Vero cell rabies vaccine and human diploid cell strain vaccine: comparison of neutralizing antibody responses to post-exposure regimens

Abstract: SUMMARYNeutralizing antibody responses to conventional rabies post-exposure regimens of human diploid cell strain vaccine (HDCSV) and the new purified Vero cell rabies vaccine (PVRV) were compared in 58 healthy Thai veterinary students. The geometric mean titres (GMTs) of the group given HDCSV were slightly higher than those given PVRV, but on day 28 the peak GMTs of the two groups were statistically similar. The early antibody response to PVRV was unaffected by the addition of passive immunization, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Combining the data from this and our four other studies using HRIG of British or French origin (Warrell et al 1983(Warrell et al , 1984Suntharasamai et al 1986;Chanthavanich et al 1987) no reaction was observed among 235 recipients, some of whom were student volunteers, but 5-5 % complained of pain at the injection 764 P. SUNTHARASAMAI AND OTHERS site. The lack of serum sickness confirms other reports of minimal complications of HRIG treatment at the usual dosage (Hattwick, Corey & Creech 1976;Nicholson & Turner, 1978;Helmick et al 1982).…”
Section: Discussionsupporting
confidence: 65%
“…Combining the data from this and our four other studies using HRIG of British or French origin (Warrell et al 1983(Warrell et al , 1984Suntharasamai et al 1986;Chanthavanich et al 1987) no reaction was observed among 235 recipients, some of whom were student volunteers, but 5-5 % complained of pain at the injection 764 P. SUNTHARASAMAI AND OTHERS site. The lack of serum sickness confirms other reports of minimal complications of HRIG treatment at the usual dosage (Hattwick, Corey & Creech 1976;Nicholson & Turner, 1978;Helmick et al 1982).…”
Section: Discussionsupporting
confidence: 65%
“…Nevertheless, the applied vaccine schedule resulted in clear seroconversion of all mice, with virus-neutralizing serum titers well above the protective threshold of 0.5 IU/ml (range 6.01–18.04 IU/ml) at the moment of challenge. Moreover, the challenge occurred at four weeks after the first vaccine administration, at the moment when the peak serological response can be expected [ 38 ; 39 ]. The height of the neutralizing antibody titer in vaccinated mice did not correspond to the level of protection upon challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as the primary culture cells inherently have a limited capacity to divide, they are technically difficult to adapt to large-scale industrial cultivation for vaccine manufacturing. For this reason, the Vero cell line was used to produce purified Vero cell rabies vaccine [24]. Vero cell cultivation can easily be scaled up and the virus titers produced in Vero cells are generally higher than those in primary culture cells.…”
Section: Brief History Of Classical Rabies Vaccinesmentioning
confidence: 99%